Profil Kinerja Keuangan Perusahaan yang Melakukan Initial Public Offering (IPO) Selama Pandemi COVID-19 di Indonesia - Lusianus Heronimus Sinyo Kelen (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
This study aims to analyze the profile of the financial performance of firms conducting IPOs during the COVID-19 pandemic through initial returns and analysis of financial statements. This research was conducted by taking a population of shares listed on the Indonesia Stock Exchange when the firm conducted an IPO during the COVID-19 pandemic from March to December 2020. In this study, the sampling method used purposive sampling, the firm listed on the IDX at the time of 51 firms conducted IPOs during the COVID-19 pandemic but the available data met the sampling criteria, thus obtaining as many as 35 firms. The analytical technique used is the descriptive analysis technique by taking data from the prospectus. The results of the first analysis show that the financial performance of firms that conducted IPOs during the COVID-19 pandemic based on initial returns was mostly in good condition so that they received a response from investors. Based on the current ratio in a good condition where the firm obtains funds that can increase liquidity as well. Based on the debt to asset ratio in a good condition where the composition of the capital structure of the firm experienced the same comparison even though it was seen from the slightly larger total debt. Based on the return on equity, most of them are in good condition where the firm's capital ability can generate high profits so that it can benefit the firm.